1996
DOI: 10.1111/j.1525-1594.1996.tb00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Low Potassium Solution (EP4 Solution) for Long‐Term Preservation of a Lung Transplant: Evaluation in Primate and Murine Lung Transplant Model

Abstract: The results of recent studies on long‐term preservation using low potassium flush solution, which was originally produced in our department, are presented and discussed. In the primate model, a lung preserved for 24 h with EP4 solution retained sufficient function in single lung allotransplantation. In the murine experiments, we have evaluated the ion transport properties across alveolar epithelial cells in the transplanted lung using the tools of alveolar fluid clearance tests. The alveolar fluid clearance ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our ECF-type solution was prepared in collaboration with Cell Science Technology (Sendai, Japan). This ECF-type solution is based on the organ-preservation solution developed for lung transplantation [12]. Because many potential solutions can be used for tissue preservation, we chose the solutions to be compared according to the following criteria: (a) the solution has been previously used for tissue preservation and/or transportation for experimental purpose; (b) the solution is chemically defined; and (c) the solution does not contain additives that can affect the stem/progenitor characteristics such as recombinant growth factors and animal serum.…”
Section: Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ECF-type solution was prepared in collaboration with Cell Science Technology (Sendai, Japan). This ECF-type solution is based on the organ-preservation solution developed for lung transplantation [12]. Because many potential solutions can be used for tissue preservation, we chose the solutions to be compared according to the following criteria: (a) the solution has been previously used for tissue preservation and/or transportation for experimental purpose; (b) the solution is chemically defined; and (c) the solution does not contain additives that can affect the stem/progenitor characteristics such as recombinant growth factors and animal serum.…”
Section: Solutionsmentioning
confidence: 99%
“…These preservation solutions are classified into two groups: intracellular fluid (ICF)-type preservation solutions (high potassium/low sodium ratio) and extracellular fluid (ECF)-type preservation solutions (low potassium/high sodium ratio) [10]. Earlier investigations exploring the use of preservation solutions for transplantation have usually employed ICF-type solutions [10]; however, more recent studies have suggested the improved functionality of the organs preserved in ECF-type solutions [11][12][13][14]. We previously demonstrated the improved viability and function of alveolar type II (ATII) cells, one of the stem/progenitor cells in lung [2], in an ECF-type solution over an ICF-type solution [15].…”
mentioning
confidence: 99%